HUBUNGAN ANTARA MOTIVASI BELAJAR DAN PRESTASI BELAJAR MATEMATIKA SISWA DALAM PEMBELAJARAN REASONING AND PROBLEM SOLVING - Kumalawati, VE Fena (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2015)
ABSTRAK Penelitian ini bertujuan untuk mengetahui: Ada tidaknya hubungan antara motivasi belajar dan prestasi belajar matematika siswa dalam pembelajaran reasoning and problem solving pada siswa kelas VII SMP. Penelitian ini merupakan penelitian kuantitatif eks-post facto dan deskripsi korelasional. Penelitian ini dilaksanakan pada siswa kelas VII semester genap tahun ajaran 2014/2015 di SMPK Santo Yusuf Madiun. Sampel dalam penelitian ini adalah kelas VIIA dan VIIB. Teknik pengambilan sampel dalam penelitian ini menggunakan porpusive sampling, sedangkan teknik pengumpulan data menggunakan metode tes dan non tes. Instrumen yang digunakan dalam metode tes adalah tes hasil belajar, sedangkan metode non tes berupa angket motivasi belajar siswa. Tes hasil belajar digunakan untuk mengetahui prestasi belajar siswa, sedangkan angket motivasi belajar digunakan untuk mengetahui motivasi belajar siswa terhadap pelajaran matematika dalam hal sikap terhadap belajar, frekuensi belajar, dan loyalitas terhadap belajar matematika. Pengujian hipotesis menggunakan uji korelasi ganda dengan taraf nyata 0,05. Untuk pengujian hipotesis hubungan motivasi belajar dengan prestasi belajar matematika Rhitung (=0,40935) > Rtabel (=0,291), maka H0 ditolak, sehingga terdapat hubungan yang positif antara motivasi belajar dengan prestasi belajar matematika pada kelas VII SMP. Besarnya hubungan motivasi belajar dan prestasi belajar siswa adalah R2 = 0,16757, sehingga dapat disimpulkan besarnya hubungan motivasi belajar dengan prestasi belajar matematika siswa dalam pembelajaran reasoning and problem solving pada siswa kelas VII SMP adalah sebesar 16,757%. Untuk pengujian koefisien regresi sikap terhadap belajar (=b1) sebesar 1,60656 diperoleh sikap dalam belajar memberi pengaruh berupa peningkatan terhadap prestasi belajar. Untuk pengujian koefisien regresi frekuensi belajar (=b2) sebesar 0,23068 diperoleh frekuensi belajar tidak memberi pengaruh terhadap prestasi belajar. Untuk pengujian koefisien regresi loyalitas terhadap belajar (=b3) sebesar 0,30552 diperoleh loyalitas terhadap belajar tidak memberi pengaruh terhadap prestasi belajar.   Kata kunci: Motivasi Belajar, Prestasi Belajar Matematika Siswa, Reasoning and Problem Solving         ABSTRACT This research is aimed to find out: The relationship of learning motivation and the students’ achievements in studying Mathematics through reasoning and problem solving strategies. This is a quantitative ex-post facto and correlation description research. The research was operated to the 7th grades of Saint Joseph Junior High School Madiun, in the even semester of 2014/2015. The sampels of the research were the students of VIIA and VIIB classes. Then, the researcher used porpusive sampling as the sampling technique, and used test and non-test methods as the data collection techniques. In the test method, the researcher used the students’ achievement test as the instrument of the research, while in the non-test method, the researcher applied a questioner concerning on students’ learning motivation. Further, the achievement test was purposed to figure out the students’ achievement, and the questioner would help to know students’ motivation in learning Mathematics especially in describing their attitude, frequency, and loyalty in learning Mathematics. A hypothesis testing in this research uses double correlation with the real level of 0.05.  After that, in testing the hypothesis of the relationship between students’ learning motivation and learning achievement in Mathematics, the researcher applies Rcount (=0,40935) > Rtable (=0,291), then H0 is rejected. From the analysis, the researcher concludes that there is a positive relationship between learning motivation and learning achievement in Mathematics of the 7th graders of Junior High School. Further, the magnitude of the relationship between learning motivation and students’ achievement is R2 = 0,16757, so that it can be concluded that the relationship of the learning motivation and the academic achievement of students in learning Mathematics through reasoning and problem solving in 7th grade of Junior High School is amounted to 16.757%. In testing the regression coefficient attitude towards learning (=b1) that is amounted 1,60656, so the attitude of learning influences on the increasing of learning achievement. Additionally, in testing the regression coefficient learning frequency (=b2) that amounts of 0,23068, so it can be said that the frequency of learning does not give any effects toward the learning achievement. Finally, in testing the loyalty of the learning regression coefficient (=b3) which is 0,30552, so it is known that the loyalty to learn does not give any effect toward the learning achievement as well.   Keywords: Learning Motivation, Students’ Achievements in Mathematics, Reasoning and Problem Solving